Relationship Between the Lecturer’s Role as Motivators to Learning Outcomes of Postpartum and Breastfeeding Midwifery Care Courses on Diploma III Midwifery Students - Sukmawati, Yofa; Winora, Okfa (Basic and Applied Nursing Research Journal, 2020)
Introduction: Education is the process of changing the attitudes and behaviors of a person or group of people through the learning and training process. The lecturer’s role as motivators to increase enthusiasm and development of lecturer learning activities is required to motivate students to obtain maximum learning outcomes. This study aims to determine the relationship between the lecturer’s role as motivators and postpartum and breastfeeding midwifery care courses' learning outcomes. Method: A type of quantitative research with analytical survey research design and cross-sectional approach. This research was conducted on diploma III midwifery students of STIKes I, with a total sample of 89 students. The data collected by using questionnaires and analyzed by Chi-Square test. Results: The results showed a significant relationship between the lecturer's role as a motivator to learning outcomes of postpartum and breastfeeding midwifery care courses, with a p-value of 0.003. Conclusion: Lecturer's role as a motivator affects postpartum and breastfeeding midwifery care courses' learning outcomes.